Accrual Accounting Practice and Financial Performance in Local Governments of Cameroon - Awasom Susana Yene Chimy; Fossung Micheal Forzeh (European Scientific Journal, ESJ, 2021)
This paper focuses on assessing the relationship between accrual accounting practice and financial performance in local governments in Cameroon. Using accountability and efficiency as performance proxies, the study employs a mix of qualitative and quantitative research approaches with a triangulate method of data collection. In a population of 374 councils, 50 councils were sampled and clustered according to their statutory council categories. Both descriptive and inferential statistics were used with a multiple regression analysis on panel data to test the relationship between accrual accounting practice and financial performance within council categories. The findings revealed that about 77% of councils (predominantly rural councils) practicing mild accrual accounting scored a higher financial performance. Meanwhile, 23% of councils (mostly city councils) practicing a moderate and sometimes strong accrual accounting had a lower financial performance. The pooled regression analysis showed a 13 % insignificant but positive correlation between financial performance and accrual accounting practice. These findings where then backed up with inferences drawn from interviews, discussions as well as content study of accounting books. It revealed that councils have the latitude to navigate from mild, moderate, and strong accrual accounting practice as the need arose. Accrual accounting practice should be sequenced in ways that councils can focus on mild accrual accounting practice, and it should move to a higher level of moderate and full accrual accounting only when they can afford the expertise and infrastructural resources needed to yield a significant performance result.